A Nest for the Soul: The Trope of Solitude in Three Early Modern Discalced Carmelite Nun-Poets. - SCHLAU, STACEY (Scripta, 2016)
For early modern Discalced Carmelite nun-poets, solitude remains tied to the paradoxical equation of life to death and death to life so famously parsed by St. Teresa. This essay examines poems by María de San Alberto (1568-1640), Ana de la Trinidad (1577-1613), and Gregoria Francisca de Santa Teresa (1653-1736) exploring the possibilities of creating and maintaining solitude while embarked on a quest for mystical union. Outstanding practitioners of the Teresian poetic tradition, the Founding Mother's religious and literary example allowed them the freedom to communicate with their religious sisters and subsequent readers, and thereby establish religious community through writing.